Grzechy Gombrowicza przeciwko wolności. O projekcie etycznym wpisanym w „Ferdydurke” - Chwin, Stefan (Wydawnictwo Naukowe UAM, 2013)
Gombrowicz’s way of thinking about freedom changed over years. He did not simply follow the ideas formulated in the 1930s. In the world presented in Ferdydurke Gombrowicz described the ontological foundations of freedom as significantly weaker than the ontological foundations of enslavement. The structure of this world was based on a strong juxtaposition of the protagonist as a lone “partisan of freedom” who feels uneasy about the constraints imposed by Form and the majority of society which is comfortable about being limited by Form and does not crave for individual freedom because it is much more afraid of falling out of Form. World War II was a turning point in the evolution of Gombrowicz’s philosophy of freedom. Before 1939 he considered the value of freedom to be unquestionable and he did not talk about its dark sides. After the war Gombrowicz also began to see freedom as a tragic gift. In his play The Marriage he showed how an individual’s pursuit of absolute freedom can turn into tyranny. The philosophy of freedom that he had formulated in Ferdydurke excluded such a possibility. In order to understand the meaning of the philosophy of distancing oneself from Form, as articulated in Ferdydurke, one should find out whether Gombrowicz directed his moral guidelines from the 1930s relating to practicing freedom only to people who lived in the interwar period, i.e. when the temperature of social tensions was moderate, or thought that it was also possible to distance oneself from Form in extreme situations, for example, during violent social conflicts, war, and occupation.
Gombrowicz’s sins against freedom. On the ethical project presented in Ferdydurke